Transforming Mutations of Jak3 (A573V and M511I) Show Differential Sensitivity to Selective Jak3 Inhibitors - Steven Martinez, G.; A. Ross, Jeremy; A. Kirken, Robert (Clinical Cancer Drugs, 2016)
Background: A medical need exists for successfully treating patients afflicted with leukemia and especially those that relapse and ultimately become refractory to front line chemotherapies. Leukemia cases are particularly high within Hispanic populations where this disease is among the most frequently occurring cancer. A possible cause is somatic mutations in Janus tyrosine kinase (Jak3). Fourteen somatic mutations have been reported in Jak3, including M511I and A573V, from patients with various forms of leukemia. While several of these Jak3 mutations have been shown to possess transforming ability in cell lines, whether these mutations are susceptible to Jak3 selective inhibitors remains less clear. Methods: The IL-3 dependent pro-B cell line Ba/F3 was virally transduced with plasmids encoding GFP and different mutant forms of Jak3, some of which conferred IL-3 independence. Sensitivity to pre-clinical and clinical Jak3 selective inhibitors was assessed for cellular viability and growth. Results: Two Jak3 mutations conferred IL-3 independent growth in Ba/F3 cells. However, the level of drug sensitivity varied with respect to Jak3 inhibitors NC1153, CP-690,550, and EP-009. Conclusion: Jak3 inhibitors CP-690,550 and NC1153 showed efficacy in reducing viability of Ba/F3 cells transformed with mutant forms of Jak3, thus providing new therapeutic strategies to treat these types of cancer.
Keywords: Janus tyrosine kinase